Best Answer

4x+3y=-15

2x-3y=-3

Take second equation and multiply the whole with 2 so that when subtracting the two equations we can cancel out x. so it becomes 4x-6y=-6

4x +3y = -15

( - ) 4x -6y = -6

----------------------------------

0x + (+3-(-6))y = -15 - (-6))

9y = -9 .. or y=-1

So take any one equation and find x by substituting y value

2x - 3(-1)= -3

2x +3 = -3

2x = -6

x = -3

So x = -3, y = -1

Q: 4x plus 3y equals -15 2x-3y equals -3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

yes

(1) x+y=15(2) 4x+3y=38From (1) one gets x=15 -y, put into(2)4(15-y)+3y=3860-4y+3y=3860-y=38y=22 then x=15-y=-7(-7,22) is the solution

That depends on what the value of x is.

-2x plus 3y equals 1

2x-11

Related questions

4.34684352143

Put the equation in this form: y=mx+b. Then m will be the slope. 2x3y+6=0 2x3y=-6 3y=-6/2x y=-2/2x y=-1/x This equation does not describe a straight line, but rather, it describes a curve.

yes

80 = 3y + 2y + 4 + 1 75 = 5y 15 = y y = 15

OK, so-3y + 15 - y = 39-3y + 15 - 15 - y = 39 - 15-3y -y = 24-4y = 24-y = 6y= -6.Hope this helps!

(2,7)

3y+5=y-25 2y=-30 y= -15

5x+3y

(1) x+y=15(2) 4x+3y=38From (1) one gets x=15 -y, put into(2)4(15-y)+3y=3860-4y+3y=3860-y=38y=22 then x=15-y=-7(-7,22) is the solution

3y + 2y + 4 + 1 = 805y + 5 = 805y = 75y = 15

That depends on what the value of x is.

-2x plus 3y equals 1